Case report: Chronic granulomatous disease presenting with early-onset inflammatory bowel disease and normal oxidative burst testing - Mondal, Sanjib; Vignesh, Pandiarajan; Loganathan, Sathish Kumar; Arora, Kanika; Das, Jhumki; Rawat, Amit; Singh, Surjit (Frontiers in Pediatrics, 2023)
Background: Due to the lack of widespread availability of flow cytometry services for immunodeficiency, nitroblue tetrazolium test (NBT) is the commonly used screening modality to identify patients with chronic granulomatous disease (CGD) in developing countries. Procedure: We report a child with X-linked CGD with residual NADPH oxidase activity who had an indeterminate NBT result even in presence of classical manifestations of CGD. Results: A 7-year-old boy presented with recurrent episodes of inflammatory colitis and Burkholderia cepacia septicemia at the age the age of 3 years. He also had cervical adenitis due to Mycobacterium tuberculosis. NBT performed at multiple occasions was not suggestive of CGD. Dihydrorhodamine test using PMA as a stimulant revealed a small blunt peak suggestive of AR-CGD, however, significant reduction in NADPH oxidase activity was noted with milder stimulants such as Escherichia coli and Staphylococcus aureus. Genetic analysis revealed a hemizygous pathogenic variant in CYBB. Flow cytometry showed diminished gp91phox expression in the patient’s neutrophils suggestive of X-linked CGD. Conclusion: Our case highlights that early-onset inflammatory bowel disease can be presenting manifestation of CGD and diagnosis of CGD can be missed if NBT alone is used for screening, especially in presence of NADPH oxidase activity. Diagnosis of “CGD with residual NADPH oxidase activity” requires high degree of clinical suspicion and performing DHR with different stimulants can unravel the diagnosis.